Prognostic implication of relative regional strain ratio in cardiac amyloidosis. Issue 10 (1st February 2016) - Senapati, Alpana; Sperry, Brett W; Grodin, Justin L; Kusunose, Kenya; Thavendiranathan, Paaladinesh; Jaber, Wael; Collier, Patrick; Hanna, Mazen; Popovic, Zoran B; Phelan, Dermot
Abstract : Objective: Cardiac amyloidosis (CA) is a rapidly progressive disease that portends poor prognosis. Our objective was to evaluate the prognostic impact of relative regional strain ratio (RRSR, a measure of the relative apical sparing of longitudinal strain (LS)) in CA. Methods: This is a retrospective study evaluating 97 patients with CA from 2004 to 2013. Patients were included if they met criteria for CA based on endomyocardial biopsy or advanced imaging criteria coupled with either extracardiac biopsy or genetic analysis. Baseline clinical and imaging data were collected and compared between light-chain amyloidosis (AL) (n=59) and transthyretin amyloidosis (ATTR) (n=38) subtypes. RRSR was defined as the average apical LS divided by the sum of the average mid and basal LS values. A Cox proportional hazards model was used to assess the effects of clinical and echocardiographic characteristics, including RRSR, on the outcome of time to death or heart transplantation. Results: Despite younger age, the AL subtype had a statistically significant association with the composite outcome as compared with ATTR (p=0.022). Log-transformed RRSR was independently associated with the composite outcome at 5 years (HR 2.45 (1.36 to 4.40), p=0.003). Patients with low ejection fraction and high RRSR had the worst prognosis. In multivariable analysis, RRSR remained predictive of the primary outcome (p=0.018). Addition of covariates related to systolic function (global LS and ejection fraction) to the model attenuated this effect. Conclusions: High RRSR is adversely prognostic in patients with cardiac amyloid. This novel tool is both diagnostic and prognostic and may have implications in management and suitability for treatment.